Hybrid Inverter Zeta-Ćuk for Grid-Tied Photovoltaic Applications - Anderson A. Dionizio; Leonardo P. Sampaio; Sergio A. O. da Silva; Vitor Monteiro; Joao L. Afonso (IEEE Open Journal of Power Electronics, 2025)
This paper proposes a novel single-phase integrated inverter for photovoltaic (PV) applications called Hybrid Inverter Zeta-Ćuk (HIZC). The HIZC operates in discontinuous conduction mode and employs four unidirectional power switches, which are achieved by associating series power diodes to MOSFETs. In addition, during the grid’s positive half-cycle, the inverter acts similarly to the Zeta converter. On the other hand, during the negative half-cycle, the inverter operates similarly to the Ćuk converter. Due to the adopted design criteria, the Zeta and the Ćuk operation modes show similar behavior. The small-signals analysis considers the Zeta and Ćuk operation modes, showing a significant similarity between their frequency responses, proofing the similarity of the HIZC’s functionality in both operation modes. The HIZC can boost the voltage of the PV array and perform the DC-AC conversion at the same time. The maximum power available at the PV array is harvested using a multi-loop control in conjunction with the perturb-and-observe algorithm, while an AF-αβ-PLL system guarantees synchronism with the power grid. Experimental results prove the structure feasibility of the proposed topology for PV applications. In addition, the HIZC presents high-efficiency conversion and also low total harmonic distortion in the current injected into the power grid.